Probabilistic Model of Back Order Policy on Dodol Pulut Raw Material Inventory Control With Linear Programming - Br Siahaan, Erika Handayani; Riri Syafitri Lubis (Department of Mathematics, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2025)
The high production costs of Dodol Pulut Raya further emphasize the importance of implementing a systematic, measurable, and effective inventory control strategy to maintain profitability, operational efficiency, and long-term business stability. This study applies the Probabilistic Back Order Policy Model combined with the Simplex Linear Programming method to determine the most optimal raw material management policy, taking into account demand uncertainty, supply variability, and the risk of stock shortages that could disrupt production smoothness. This approach comprehensively integrates precise safety stock calculations to minimize stockouts, reduce production delays, and ensure raw material availability so that customer needs can be consistently, timely, and sustainably met. The analysis results show that the implementation of this model can significantly reduce annual production costs from IDR 509,941,040 to IDR 338,719,300, resulting in cost efficiency of IDR 171,221,740 per year. This finding demonstrates the model's effectiveness in minimizing total inventory costs while enhancing competitiveness and operational sustainability. Additionally, this study provides a practical framework for small and medium-sized enterprises facing fluctuating demand, balancing service levels, safety stock, and overall cost optimization.